United States Protectionism Through Import Tariffs for Canada and Reciprocity - SULISTYAWATI, Rr Laeny (Journal of Political And Legal Sovereignty, 2024)
Purpose:This paper explores the changing foreign policy of the United States (US) after Donald Trump took office as president for the second time, namely through the America First policy. The America First policy includes protectionist measures such as import tariffs on Canadian products of 25 percent on March 4, 2025.Methodology:The research method uses qualitative descriptive analysis. Data were collected through data collection techniques based on internet-based studies, digital books, previous research, journals and relevant sources.Findings:Canada is one of the largest exporting countries in the US with a total of 37.253 billion US during 2024. However, after President Trump was re-elected, economic relations between the US and Canada became heated. President Trump implemented an import tariff policy from Canada on the grounds of illegal immigration and fentanyl drugs. This policy is expected to protect jobs and increase income.Implication:However, government of Canada took retaliatory action by implementing 25 percent import tariff policy on imported goods from the US. Several businesses in Canada, particularly café industry, expressed support for the government’s policy. The Canadian government also increased the budget to increase security at the border.